MySQL phrasebook : essential code and commands - Greant, Zak (Sams, 2006)
The MySQL Phrasebook is a pocket guide that is jam-packed with useful and essential code "phrases" for the MySQL developer's everyday use. Packed with practical solutions for tasks that the MySQL developer must accomplish every day, it fills the need for a short, functional, to-the-point reference for MySQL. This is the guide to consult when you need an immediate, applicable solution to frequent tasks and code that is flexible and adaptable to your needs. Your time won't be wasted on more tutorials -- it simply puts essential "phrases" at your fingertips that you can take with you everywhere.